Advancing practice-oriented education in the training of future pedagogic psychologists - Manashova, Gulmira; Mirza, Natalya; Beisenbekova, Gulmira; Nurgaliyeva, Saule; Korzhumbayeva, Maral (International Journal of Evaluation and Research in Education (IJERE), 2025)
This research aims to explore the characteristics of practice-oriented training within universities and identify the psychological and pedagogical factors that influence the development of professional competencies in future specialists. A comprehensive combination of content analysis of training conditions for future professionals in higher education and an analytical review of the formation of professional competencies among teacher-psychologists in the context of educational system modernization were applied. The conclusions highlight the challenges of implementing practice-oriented training in Kazakhstan’s higher education system, detailing its forms and methods in preparing competitive and competent specialists. Additionally, the study addresses strategies for effectively organizing pedagogical conditions that foster the development of core competencies in future professionals within social and psychological fields. The findings are critical for educators educating future teacher-psychologists, as they emphasize practice-oriented methods during educational modernization.